Effects of high-altitude hypoxic environment on colonic inflammation, intestinal barrier and gut microbiota in three-way crossbred commercial pigs - Luo, Chengzeng; Sun, Guangming; Duan, Jiujun; Han, Haiyu; Zhong, Ruqing; Chen, Liang; Wangdui, Basang; Zhu, Yanbin; Wang, Zirong; Zhang, Hongfu (Frontiers in Microbiology, 2022)
In recent years, the three-way crossbred commercial pigs are extensively cultured in Tibet. However, there have been few studies about the effect of high-altitude hypoxic environment on intestinal health of them. Therefore, we selected Tibetan pigs (TP) and the three-way crossbred commercial pigs (CP-H) living in the Tibet (3,500-3,700 m in altitude) as a positive control group and treatment group, respectively. The three-way crossbred commercial pigs (CP-L) living at altitudes 800-1,000 m sea level were selected as a negative control group. The colonic chyme, colonic mucosa, colonic tissue and serum samples were collected for the detection of gut microbiota and intestinal inflammation. The results showed that high-altitude hypoxic environment promoted the occurrence of colonic inflammation, disrupted the colonic barrier to some extent. And Hematoxylin–Eosin (HE) staining revealed that mild inflammatory cell infiltration was observed in colon of CP-H. 16S rRNA gene sequencing revealed that the microbial community composition of CP-H was changed compared with CP-L. Gut bacterial communities formed distinctly different clusters in principal coordinates analysis (PCoA) space, and Chao 1 index of CP-H was also decreased. At the genus level, Terrisporobacter showed greater enrichment in the CP-H than lower-altitude pigs. Colstridium-sensu-stricto-1 showed lower enrichment in the CP-H than lower-altitude pigs. However, the concentration of valeric acid in colonic chyme of CP-H was higher than CP-L and TP. Correlation analysis indicated that Terrisporobacter was positively associated with the relative mRNA expression level of IL-1β and the content of lipopolysaccharide (LPS), and was negatively correlated with the relative mRNA expression level of IL-10. The Streptococcus was positively associated with the concentrations of valerate. In summary, high-altitude hypoxic environment changed compositions of gut microbiota, promoted the occurrence of colonic inflammation, and disrupted intestinal barrier of the three-way crossbred commercial pigs.